Anti-inflammatory effects of isorhamnetin on LPS-stimulated human gingival fibroblasts by activating Nrf2 signaling pathway. (July 2018) - Qi, Feng; Sun, Ji-hao; Yan, Jia-qun; Li, Chun-mei; Lv, Xue-chao
Abstract: Periodontitis is a highly prevalent infective and inflammatory disease with an adverse impact on systemic health. Isorhamnetin, a flavonoid mainly isolated from Hippophae fhamnoides L. fruit, has been reported to have anti-inflammatory effect. This study aimed to investigate the anti-inflammatory effects and mechanism of isorhamnetin on lipopolysaccharide (LPS)-induced inflammatory response in human gingival fibroblasts (HGFs). The production of inflammatory mediators and the expression of proteins were measured by ELISA and western blot analysis. The results demonstrated that isorhamnetin attenuated LPS-induced release of PGE2, NO, IL-6, and IL-8 in HGFs. Isorhamnetin also inhibited LPS-induced NF-κB activation. The expression of Nrf2 and HO-1 were up-regulated by treatment of isorhamnetin. Furthermore, knockdown of Nrf2 by siRNA reversed the anti-inflammatory effects of isorhamnetin. In conclusion, these results suggested that isorhamnetin inhibited LPS-induced inflammation in HGFs by activating Nrf2 signaling pathway. Highlights: Isorhamnetin attenuated LPS-induced release of PGE2, NO, IL-6, and IL-8 in HGFs. Isorhamnetin also inhibited LPS-induced NF-κB activation. The expression of Nrf2 and HO-1 were up-regulated by treatment of isorhamnetin. Knockdown of Nrf2 by siRNA reversed the anti-inflammatory effects of isorhamnetin.